Probiotics in Human Immunodeficiency Virus Infection: A Systematic Review and Evidence Synthesis of Benefits and Risks. (29th July 2016) - Carter, George M.; Esmaeili, Aryan; Shah, Hardikkumar; Indyk, Debbie; Johnson, Matthew; Andreae, Michael; Sacks, Henry S.
Abstract : The risk of sepsis is low. The best probiotic to optimize outcomes has not yet been identified. Potential benefit for CD4 count, recurrence or management of bacterial vaginosis and diarrhea. Uncertain effect on translocation, BV treatment. Abstract: People living with human immunodeficiency virus frequently use dietary supplements, including probiotics, but concern exists about ingesting live organisms. We performed a systematic review of the benefits of probiotics and a meta-analysis of sepsis risk. We undertook a protocol-driven, comprehensive review to identify all relevant studies, assess their quality, and summarize the evidence. Of 2068 references, 27 were analyzed. The data suggest possible benefits for CD4 count, recurrence or management of bacterial vaginosis, and diarrhea management. We examined randomized, controlled studies explicitly assessing sepsis in any patient population, and we found zero cases of supplement-associated bacteremia or fungemia in 39 randomized controlled trials comprising 9402 subjects. The estimated number needed to harm is 7369 in Bayesian approach (95% credible interval: 1689, ∞), which should reassure clinicians. No or mild adverse effects were reported. Longer duration studies investigating different individual and mixed strains for plausible indications are needed to establish best practices.